2004
DOI: 10.1007/s11906-004-0084-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic issues in the antihypertensive and lipid-lowering heart attack trial study

Abstract: Based on the Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack (ALLHAT) Trial, the Seventh Joint National Committee on Prevention, Detection, Evaluation and Treatment of High Blood Pressure (JNC-7) states that "thiazide-type diuretics should be used as initial therapy for most patients with hypertension." In the ALLHAT study, although there was no difference in the primary outcome for fatal heart attack and nonfatal myocardial infarction between all treatment groups, the manuscript endorses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…3,5,24,25 In ALLHAT, development of diabetes occurred significantly more in the thiazide group with an absolute difference of 1.8% to 3.5% relative to the lisinopril and amlodipine groups (PϽ0.05). In other clinical trials, the absolute difference of new-onset diabetes was 2.1% and 1.6% higher in the thiazide diuretic groups compared with ACE inhibitor or CCB groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,24,25 In ALLHAT, development of diabetes occurred significantly more in the thiazide group with an absolute difference of 1.8% to 3.5% relative to the lisinopril and amlodipine groups (PϽ0.05). In other clinical trials, the absolute difference of new-onset diabetes was 2.1% and 1.6% higher in the thiazide diuretic groups compared with ACE inhibitor or CCB groups.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some have argued that the follow-up period of 4.9 years (range, 4 to 8 years) was not adequate to account for the occurrence of cardiovascular outcomes among those patients who developed diabetes while receiving antihypertensive treatment. 3,4 Reports by Verdecchia et al 5,6 seem to support this view. They observed that treatment with thiazide diuretics was an independent predictor of new diabetes among patients with hypertension, followed for a median of 6 years (range, 1 to 16 years).…”
mentioning
confidence: 93%
“…All M t measurements which utilized this technique so far lacked a consistent likelihood formulation owing to the absence of the resolution prior, as discussed in detail in [137]. Perhaps, this is the reason why such measurements did not demonstrate convincing uncertainty improvements over results obtained with templates.…”
Section: Methods Based On Distribution Fittingmentioning
confidence: 99%
“…Prior to the selection of multiple candidates (see below), we make the requirement |∆E| < 0.30 GeV, in order to retain sidebands for background studies. However, to avoid possible biases [31] we do not use ∆E in the fit described below and instead apply tighter selection criteria for events entering the fit, −0.15 GeV < ∆E < 0.05 GeV. These criteria have an efficiency of about 80 % for signal while retaining only about 30 % of the background, both compared to the looser requirement |∆E| < 0.30 GeV.…”
Section: Event Reconstruction and Selectionmentioning
confidence: 99%